2007
DOI: 10.1016/j.nima.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

An experiment for two-color photoionization using high intensity extreme-UV free electron and near-IR laser pulses

Abstract: We describe an experimental system designed for single-shot photoelectron spec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…This laser is essentially a copy of the photocathode laser producing the electron pulses for the FEL and can thus provide the same pulse pattern as the FEL 21 . The actively mode-locked oscillator of the laser system allows a synchronization better than 1 ps jitter to the XUV pulses of the FEL 22 . This laser was focused to an approximately 30 mm FWHM spot on the sample and delivered approximately 25 mJ per pulse, producing fluences on the sample of between 2 and 6 J cm 22 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This laser is essentially a copy of the photocathode laser producing the electron pulses for the FEL and can thus provide the same pulse pattern as the FEL 21 . The actively mode-locked oscillator of the laser system allows a synchronization better than 1 ps jitter to the XUV pulses of the FEL 22 . This laser was focused to an approximately 30 mm FWHM spot on the sample and delivered approximately 25 mJ per pulse, producing fluences on the sample of between 2 and 6 J cm 22 .…”
Section: Methodsmentioning
confidence: 99%
“…The actively mode-locked oscillator of the laser system allows a synchronization better than 1 ps jitter to the XUV pulses of the FEL 22 . This laser was focused to an approximately 30 mm FWHM spot on the sample and delivered approximately 25 mJ per pulse, producing fluences on the sample of between 2 and 6 J cm 22 . The pulse length for the pump laser was 12.5 ps, giving peak intensities of about 2.2 Â 10 11 W cm 22 on the sample, adequate to fully destroy the sample in a single pulse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the measurement capabilities of FELs are currently limited to 100 fs by the timing stability of the electron beams and the synchronization capabilities between the electron beams and the optical lasers. Conventional microwave timing synchronization, which is based on coaxial cables, has difficulties in achieving even ps long-term stability as a result of the large timing drifts over the extent of a FEL [99]. As a remedy for this timing problem, it has been shown that the post-processing of X-ray pulse arrival time can be used to reduce the timing uncertainty to the 60-fs level [100].…”
Section: Large-scale Optical and Microwave Timing Synchronization Sysmentioning
confidence: 99%
“…The experiments were performed on beam line BL2 at FLASH using an experimental setup for electron spectroscopy similar to that described earlier [11]. The FEL was operated in single-bunch mode at a 5 Hz repetition rate and fundamental wavelengths of 26.9 nm (46 eV) with a mean pulse energy of 10-15 J as measured on line for each pulse using a gas-monitor detector [12].…”
mentioning
confidence: 99%